2018
DOI: 10.1177/1071100717751183
|View full text |Cite
|
Sign up to set email alerts
|

Union Rate and Rate of Hardware Removal Following Plate Fixation of Metatarsal Shaft and Neck Fractures

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
1
7
0
6
Order By: Relevance
“…18 However, fractures with axis deviation of more than 20° or associated instability are better treated with surgery (k-wires or plate and screws 6 Actually, restoring anatomic alignment in unstable metatarsal fractures is the goal in operative management, because is important and necessary for pain-free deambulation. 9 When pseudoarthrosis occurs, the aim of treatment is to guarantee the stability of the fracture. In this patient, pseudoarthrosis was treated with plate and screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, fractures with axis deviation of more than 20° or associated instability are better treated with surgery (k-wires or plate and screws 6 Actually, restoring anatomic alignment in unstable metatarsal fractures is the goal in operative management, because is important and necessary for pain-free deambulation. 9 When pseudoarthrosis occurs, the aim of treatment is to guarantee the stability of the fracture. In this patient, pseudoarthrosis was treated with plate and screws.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The invasive therapeutic strategies includevarious types of graft (autologous bone graft, vascularized bone flap graft and allograft), internal fixation with plate and screws, K-wires or intramedullary nail. 7,9 A case of a 10 years old child with pseudoarthrosis of the second metatarsal is discussed. We achieved a successful outcome after osteosynthesis with plate and screws.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bowes and Buckley noted that intramedullary screw fixation using 4.5-mm malleolar screws resulted in re-fracture and may cause delayed union or non-union in Jones fractures[ 6 ]. However, in a round table discussion by Carpenter et al [ 27 ] and recent studies by Bryant et al [ 28 ], O'Malley et al [ 29 ] and Tan et al [ 30 ], this method offers a higher rate of healing among athletes, with lower re-occurrence of fractures. Thus, based on this argument, it could be concluded that the utilization of larger diameters during surgery may help to prevent future fracture.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Mehrfragmentäre, dislozierte Frakturen mit Gelenkbeteiligung erfordern eine offene Reposition und interne Fixierung mittels Platten‑/Schraubenosteosynthese [ 18 ]. In diesen Fällen zeigt die Versorgung mittels Plattenosteosynthese gute Ergebnisse mit knöcherner Konsolidierung und zeitnaher Vollbelastung [ 8 ]. Komplexe Verletzungen des Mittelfußes mit Trümmerfrakturen und signifikantem Weichteilschaden können jedoch auch zu dauerhaften Beschwerden führen [ 2 ].…”
Section: Hintergrund Und Fragestellungunclassified
“…Mittelfußknochens analysieren [ 7 , 20 ]. Darüber hinaus sind bei diesen retrospektiven Studien, welche sich mit dem operativen Ergebnis von Mittelfußfrakturen beschäftigten, nur weniger als 50 Patienten untersucht worden [ 8 , 13 ]. Es existiert lediglich eine größere Studie mit mehr als 300 Patienten von Cakir et al., die das funktionelle Ergebnis nach konservativer Behandlung von Mittelfußfrakturen untersuchten [ 9 ].…”
Section: Hintergrund Und Fragestellungunclassified